1975
DOI: 10.2307/1421596
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of a Model's Performance on an Observer's Electromyographic Activity

Abstract: It is suggested that motor reactions may be elicited in an observer as a consequence of his exposure to a model and that such reactions may become conditioned to environmental events. An experiment is reported in which observers showed greater EMG activity in the arm while watching models arm wrestle than while watching a model stutter, and greater lip EMG activity while watching a model stutter than while watching arm wrestling. Some evidence for conditioning was found in the arm activity of males watching wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 8 publications
3
48
0
Order By: Relevance
“…We used hand and foot actions that not only are routinely performed by both effectors, but that also share a high degree of spatial-configural overlap, in order to dissociate the effects of body part observation from those of movement observation. Our findings extend those of previous behavioral studies on body part priming Bach et al, 2007;Berger and Hadley, 1975) by showing that it occurs even when actions are matched on the movement dimension, and by demonstrating that body part priming gives rise to automatic imitation.…”
Section: Body Part Priming and Somatotopy In The Mirror Neuron Systemsupporting
confidence: 88%
See 1 more Smart Citation
“…We used hand and foot actions that not only are routinely performed by both effectors, but that also share a high degree of spatial-configural overlap, in order to dissociate the effects of body part observation from those of movement observation. Our findings extend those of previous behavioral studies on body part priming Bach et al, 2007;Berger and Hadley, 1975) by showing that it occurs even when actions are matched on the movement dimension, and by demonstrating that body part priming gives rise to automatic imitation.…”
Section: Body Part Priming and Somatotopy In The Mirror Neuron Systemsupporting
confidence: 88%
“…Akins and Zentall, 1996;Bach and Tipper, 2007;Berger and Hadley, 1975;Dawson and Foss, 1965;Voelkl and Huber, 2000), but, on closer examination, it becomes clear that none of these studies isolated the effects of effector observation from those of movement observation.…”
Section: The Mirror Neuron System and Imitationmentioning
confidence: 99%
“…Allers and Scheminzky (1926) recorded electromyographic (EMG) activity of human participants while they imagined performing certain actions, and the experimenters were able to ''guess'' the imagined action from the amplified, audible signal (see also Jacobson, 1932;Wehner, Vogt, & Stadler, 1984). Berger and Hadley (1975) studied EMG correlates of action observation and found that arm EMG activity was stronger when participants watched wrestling actions, and that lip EMG activity was stronger for stuttering. Although the phenomenon of motor involvement during representing actions, either via imagery or during observation, was thus known for a long time, its cortical mechanisms were left unspecified by these early studies.…”
Section: Mirror Neurons In the Macaque Monkeymentioning
confidence: 99%
“…For example, an observer with a foot shaking model may be more likely to perform a variety of foot movements -not just foot shaking -than an observer with a face-rubbing model, and this difference may be greater when the observers have more positive social attitudes. Non-specific effects of this kind are known in the motor control literature as 'effector priming' (Bach & Tipper, 2007;Berger & Hadley, 1975;Gillmeister, Catmur, Brass & Heyes, in press). …”
mentioning
confidence: 99%